Utilizing Two Maximum Power Point Tracking Techniques with an Integrated DC-DC Boost Converter for Controlling a Grid-Connected Photovoltaic‎ SystemPPT Techniques combined with an Integrated DC-DC Boost Converter for Controlling a Grid-Connected PV System - Elbahat, Haitham Ibrahim; Fawzy, Ibram Y.; Diab, Ahmed A. Zaki; Sultan, Hamdy; Kassem, Ahmed; Maarif, Alfian; Mossa, Mahmoud A. (Buletin Ilmiah Sarjana Teknik Elektro, 2026)
This paper focuses on the comparison of maximum power point tracking ‎‎(MPPT) techniques for photovoltaic (PV) system that is interfaced with the ‎utility ‎grid via a three-phase voltage source inverter (VSI). Two algorithms for ‎MPPT ‎are presented: the Perturb and Observe (P&O) technique and the ‎Incremental Conductance (INC) algorithm, ‎which employ a DC-DC boost ‎converter.‎ The algorithms are designed to optimize the capture of power produced by the PV system by measuring the PV output power and adjust the converter’s duty cycle. The VSI in the system handles the conversion from DC to AC. It employs both an internal control loop and an external control loop to maintain the stability of the DC-link voltage and to ensure synchronization with the grid. The grid synchronization of system involves the use of Phase-Locked Loops (PLL) to achieve high accuracy in dynamic conditions. The MPPT algorithms are implemented purely in a simulated environment using the Matlab/Simulink package to illustrate the advantages of the presented MPPT methods in comparison to operating without MPPT under different meteorological conditions. The PV array simulation generally employs monocrystalline modules. The electrical parameters of the system comprise the maximum power point voltage (Vmpp), maximum power point current (Impp), open-circuit voltage (Voc), and short-circuit current (Isc). The system initiates operations under standard test conditions (STC) of 25°C and 1000 W/m² during the simulation, followed by variations in irradiance (G) and temperature (T) over time. The findings‎ indicate that the P&O technique effectively tracks the maximum power point (MPP) and facilitates the extraction of further power throughout fluctuations under various meteorological conditions. Furthermore, the INC algorithm is determined to be more effective for achieving MPPT in relation to both the P&O method and the absence of MPPT under dynamic as well as steady-state conditions‎. The INC algorithm is shown to increase the PV output power at STC by 5.24% without utilizing ‎MPPT, whereas the P&O algorithm achieves an enhancement of 3.24%.‎ The results also reveal that the INC technique exhibits the highest performance, achieving approximately 99.72% efficiency, whereas P&O reaches nearly 97.62% efficiency at STC.